A History of Drill Consumable Control at Renison Mine - Davison GR (The Australasian Institute of Mining and Metallurgy, 1985)
The cost of drilling consumables is always a large component of any mine budget. It is important that this cost be carefully examined with a view to reducing the overall cost per inetre or at least minimising its escalation.At Renison it is considered that the only way to ensure drilling costs do not rise unduly is through a total system of control from purchase to disposal.In 1979 extension of an existing drill supply service contract was carefully examined and abandoned in favour of a hybrid system. This system is providing a great deal of control over the use of drilling consumables and has maintained a relatively constant cost per drilled metre over the last five years.Current consignment stock contracts for drilling consumables are strictly specified by the Technical Services section of the Mine Department and consumables purchased under these contracts are distributed and refurbished/sharpened by a contractor.The total result of this package is individual drilling items that achieve the best cost per metre and careful distribution and maintenance to ensure maximum life.